Supraclavicular lipoblastoma - Austin Lunney; Karla Leal; John Fitzwater (Elsevier, 2019)
Introduction: Lipoblastoma is a rare soft tissue tumor that occurs mainly in the abdomen and extremities in infants and children, however, few cases have been found in the neck. Presentation of case: We present a case of a 19-month-old male that had an enlarging mass on the left cervical region of his neck. He underwent an en bloc resection and pathology described a lipoblastoma. He had no post-operative complications. Discussion: Although benign, lipoblastomas have an incredibly high recurrence rate if not resected completely. They can present anywhere in the body, but very few reports have been published in the cervical region of the neck. It should be on the differential diagnosis of a fatty mass in a child or infant. Conclusion: It is important to understand the pathology and differential diagnosis of a lipoblastoma. A liposarcoma is a malignant possibility of a fatty mass and must be ruled out as some types can resemble a lipoblastoma pathologically. Keywords: Lipoblastoma, Cervical mass, Infant, Liposarcoma